Survey of entomopathogenic nematodes and fungi in agricultural areas - Magdalena Dzięgielewska; Iwona Adamska (Plant Protection Science, 2020)
In 2016-2018, in north-western Poland, field studies were carried out on the coexistence of various taxonomic groups, such as soil nematodes and fungi, including beneficial species that comprise the environment's natural resistance to pests in agrocenoses. The research aimed to find a connection between select biotic and abiotic factors in the chosen crops which could have practical applications in plant protection. Entomopathogenic nematodes Steinernema feltiae Filipiev, 1934 and entomopathogenic fungi Cordyceps fumosorosea and Metarhizium anisopliae (Metschn.) Sorokin were found to be present in all studied agrocenoses; however, they showed clear preferences for some types of crops or soil. The research shows that the effectiveness of the biological methods of plant protection depends on the selection of the right biopreparations, which strengthen the local populations of the beneficial organisms present in specific agriculture areas.